The Neutral State: A Genealogy of Ecosystem Service Payments in Costa Rica - David M Lansing; Kevin Grove; Jennifer L Rice (Conservation & Society, 2015)
Using the case of Costa Rica, this paper examines how ′carbon′ became an identifiable problem for that state. We trace how, during the 1980s, rationalities of financialisation and security arose in this country that allowed for Payments for Ecosystem Services (PES) to emerge as an economic and political mechanism. Our central thesis is: this period initiated a government project of securing a viable future for the nation′s resources by linking them to global financial markets and international trade. This project of achieving resource security through economic circulation introduced new financial logics into forest management, as well as new modes of calculating the value and extent of the forest. These ways of framing resources found expression in the nation′s PES programme that is now central to the state′s goal of achieving carbon neutrality. Today, Costa Rica′s carbon flows are becoming territorialised as part of the nation′s atmosphere, biomass, people, and economy. This paper shows how carbon′s territorialisation did not begin with a concern for the climate, nor did it occur through diffusion of global climate policy to Costa Rica. Instead, carbon′s rise can be traced to locally specific ways of coping with the problem of resource security.